2014
DOI: 10.1519/jsc.0b013e3182986cc1
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Muscle Mechanics Associated With Anterior Cruciate Ligament Deficiency and Reconstruction

Abstract: Isometric and isokinetic knee strength deficits were examined on patients with anterior cruciate ligament (ACL) injury before and after ACL reconstruction. Muscle strengths of the uninjured and injured knees were measured from an ACL injured (n = 12) and a control (n = 15) group. Five isometric (10, 30, 50, 70, and 90° of knee flexion) and 5 isokinetic (50, 100, 150, 200, and 250°·s) strengths of quadriceps and hamstrings were measured prereconstruction and postreconstruction (3 and 6 months). Compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…ACL-D subjects showed a deficit of the peak quadriceps torque in both isometric testing in males (Urbach, et al, 2001) and isokinetic testing (Konishi, et al, 2011;Tsepis, et al, 2004) in males and females. Another study found quadriceps and hamstring deficits for isometric and isokinetic tests in male and females (Hsiao, et al, 2014). In contrast, one study found greater isokinetic hamstring strength in ACL-D females (Swanik, et al, 2004).…”
Section: Muscular Capacitymentioning
confidence: 97%
See 4 more Smart Citations
“…ACL-D subjects showed a deficit of the peak quadriceps torque in both isometric testing in males (Urbach, et al, 2001) and isokinetic testing (Konishi, et al, 2011;Tsepis, et al, 2004) in males and females. Another study found quadriceps and hamstring deficits for isometric and isokinetic tests in male and females (Hsiao, et al, 2014). In contrast, one study found greater isokinetic hamstring strength in ACL-D females (Swanik, et al, 2004).…”
Section: Muscular Capacitymentioning
confidence: 97%
“…Two studies demonstrated weaknesses in quadriceps strength that were still present at both 1 and 3 months after injury in males and females during isometric and isokinetic contraction (Drechsler, et al, 2006;Hsiao, et al, 2014). Another study also found a decrement of isokinetic strength in the quadriceps in males (Xergia, et al, 2013).…”
Section: Muscular Capacitymentioning
confidence: 98%
See 3 more Smart Citations